TEORI LOKASI DENGAN PENDEKATAN PARTIAL EQUILIBRIUM DALAM KEBIJAKAN EKONOMI REGIONAL (Fokus Ekonomi, 2008)
Location theori in the regional economy policy deals with the decision on the determination of the economic activity by considering the selling output and input. Among the various approaches used determine the location, the Partial Equilibrium is one of the economic activity units that can be explored. There are 3 (three) factors analyzed, they are the transportation orientation, the competition to have control over the market, and the competition to obtain the workforce. The partial Equilibrium approach also analyzes the effect resulted by the determination of the economic activity location that is known as agglomeration. The agglomeration effect appears throught the bias of economic scale that has either positive or negative effect for the nearby location. Key Words: Regional Economic Policy, Partial Equilibrium Approach , Agglomeration